2017
DOI: 10.1016/j.sbi.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of mammalian bHLH-PAS transcription factors

Abstract: The mammalian basic helix-loop-helix-PER-ARNT-SIM (bHLH–PAS) transcription factors share common architectural features that include a bHLH DNA-binding domain and tandemly positioned PAS domains. The sixteen members of this family include the hypoxia-inducible factors (HIF-1α and HIF-2α), ARNT (also known as HIF-1β), CLOCK and BMAL1. Most bHLH-PAS proteins have been genetically linked to variety of diseases in humans, including cancers, metabolic syndromes and psychiatric conditions. To function as transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 55 publications
4
79
0
Order By: Relevance
“…Firstly, based on the average ΔG bind results of 3 apo systems, we can find that the value of binding free energy between HIF‐2α and ARNT for apo 2 (−25.09 ± 2.37 kcal/mol) is lower than that of apo 1 (−16.12 ± 2.89 kcal/mol) and apo 3 (−7.82 ± 1.19 kcal/mol), given that apo 2 is thermodynamically much more stable than apo 1 and apo 3. The result indicates that the second binding model from the PAS‐B domain of full‐length HIF‐2 may be dominate in solution, which is consistent with the viewpoints of Wu et al Compared with the respective apo system, the binding free energy between 2 monomers is reduced in the 3 PT2399‐bound systems (C1‐PT2399, C2‐PT2399, and C3‐PT2399). It means that the protein‐protein interactions of 3 models are disrupted as the binding of PT2399, which verifies the speculation from Rg analyses.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Firstly, based on the average ΔG bind results of 3 apo systems, we can find that the value of binding free energy between HIF‐2α and ARNT for apo 2 (−25.09 ± 2.37 kcal/mol) is lower than that of apo 1 (−16.12 ± 2.89 kcal/mol) and apo 3 (−7.82 ± 1.19 kcal/mol), given that apo 2 is thermodynamically much more stable than apo 1 and apo 3. The result indicates that the second binding model from the PAS‐B domain of full‐length HIF‐2 may be dominate in solution, which is consistent with the viewpoints of Wu et al Compared with the respective apo system, the binding free energy between 2 monomers is reduced in the 3 PT2399‐bound systems (C1‐PT2399, C2‐PT2399, and C3‐PT2399). It means that the protein‐protein interactions of 3 models are disrupted as the binding of PT2399, which verifies the speculation from Rg analyses.…”
Section: Resultssupporting
confidence: 87%
“…domain of full-length HIF-2 may be dominate in solution, which is consistent with the viewpoints of Wu et al17,50 Compared with the respective apo system, the binding free energy between 2 monomers is reduced in the 3 PT2399-bound systems (C1-PT2399, C2-PT2399, and C3-PT2399). It means that the protein-protein interactions of 3 models are disrupted as the binding of PT2399, which verifies the speculation from Rg analyses.…”
supporting
confidence: 89%
“…Interestingly, a crystal structure of a another member of the bHLH-PAS heterodimeric protein family, HIF-2α-ARNT, reveals a completely different overall domain arrangement when compared to CLOCK:BMAL1, but specific domain interface interactions are preserved between the respective bHLH, PAS-A and PAS-B domains of the two subunits 164 (see REF. 165 for a comparison of these bHLH-PAS structures). The recognition of the CACGTG E-box DNA binding motif of the CLOCK:BMAL1 bHLH region is similar to that seen for other bHLH proteins 166 .…”
Section: Introductionmentioning
confidence: 99%
“…Our pan-cancer integrated analyses demonstrated that the circadian clock had both tumour-promoting and tumour-suppressing qualities that were cell-type dependent. Tumour hypoxia is linked to disease aggression and therapeutic resistance (22).Hypoxia inducible factors (HIFs), the master regulators of hypoxia signalling, are transcription factors containing PER-ARNT-SIM domains and are structurally analogous to core clock proteins BMAL1 and CLOCK (23)(24)(25), suggesting that both pathways can be co-regulated. Indeed, past reports have shown that hypoxic responses are gated by the circadian clock (26,27).…”
Section: Introductionmentioning
confidence: 99%